Exemption from Penalty: A Jurisprudential Study Compared to Positive Law - Al Sheehah, Ahmad Abdulrahman (Journal of Posthumanism, 2024)
Exemption from penalty means not implementing the criminal penalty imposed on the incident if one of the legal reasons for waiver is achieved. The study has explained the concept of punishment, its divisions and purposes, the cases that call for not implementing the criminal punishment, and what those cases entail in terms of implementing the principle of forgiveness and tolerance, and the actual application of the legal purposes of punishments in Islam to deter and reform criminals, and achieve security and ensure the establishment of public order in society. The research has shown that the purpose of punishment in the Islamic system is not to take revenge on the offender or to torment him, but rather the aim is to deter and reform him, and to restore things to their proper place so that life among people may be straightened out. If this is achieved through the offender’s repentance, reformation, and voluntarily returning rights to their rightful owners, then there is no need to torture him or impose punishment on him. Rather, it is better for him and for society to help him adopt upright behavior and a correct life, so that he may be a good and beneficial individual to himself, his family, and society.